HEAVY METAL REMOVAL AT SOLUTION WITH NATURAL ZEOLITE - Saryati Saryati; Supardi Supardi; Supandi Suminta; Rohmad S. (Institut Teknologi Bandung, 2010)
This research studied the effect of chemical activation processes of natural zeolite to heavy metal removing efficiency (%) and chemical composition of natural zeolite. The solutions 0,5M of HCl,NH4OH, KOH and NaOH was used as an activator. Heavy metal solutions (Cu, Cd, Pb, Zn, Fe and Mn) of 50 ppm was used as sample. Chemical composition of zeolite was viewed semi-quantitatively using a SEM EDX. The result indicate that Si/Al ratio was decreased because alkali activity and increased because the acid activity. The efficiency of zeolite without chemical activation on disposal heavy metals in water reached above 80% for Cd,Pb,Cu and Fe, 44% for Zn and 21% for Mn. Activation of natural zeolite with acid generally reduce the efficiency, except Fe and Pb, whereas activation with mineral salts and alkaline generally increase disposal heavy metal efficiency.